A eugenia : um estudo a partir do contraponto entre a teoria bioconservadora de Jürgen Habermas e a teoria liberal de Ronald Dworkin - Meurer, Quétlin Nicole (My University, 2016)
Bioethics, genetic and in particular, eugenics, have aroused great interest and concern in sev-eral knowledge areas. The discoveries in genetics make it possible to discover the cure of cer-tain diseases, on the other hand, leads to consequent concern about the ethics of human behav-ior in that area and the dreaded racial cleansing. Thus, the present work is the contrast be-tween the bioconservative design Jürgen Habermas and the liberal conception of Ronald Dworkin, considering the antagonism of both theories from an ethical and moral point of view. After contextualizing the problem in the philosophical horizon, first, they present the Habermasians arguments against liberal eugenics through the analysis of the work The Future of Human Nature: towards a liberal eugenics? It will explain the Habermas's arguments in favor of the ethics of the species from the concepts of equality, reciprocity, autonomy, self-determination, dignity, beyond the self-understanding of individuals as free and equal beings. Searching, therefore, to reconstruct Habermas's argumentative strategy. Later, criticizing the bioconservatives arguments of Jürgen Habermas, especially in relation to positive eugenics (human enhancement) and the foundation of their ideas in relation to the normative under-standing of human relationships. The debate around the issue of post-humanity with support in the liberal theory of Ronald Dworkin, as this stage is considered a result of biotechnology and makes a crucial point of disagreement between the two theories. The American philoso-pher picks a side in favor of the right of reproductive freedom and, consequently, in favor of the submission of the means of human improvement to freedom of choice. Therefore, this paper aims to provide elements for which they verify the boundaries of genetic manipulation, so that it is up to morality and ethics to fill the vacuum of fate created by biotechnology, tak-ing aim at maintaining the species and the human nature.
A bioética, a genética e, em especial, a eugenia, tem suscitado grande interesse e preocupação das diversas áreas do conhecimento. Se por um lado as descobertas na área da genética possibilitam a descoberta de cura de determinadas doenças, por outro, leva à consequente preocupação sobre a ética das condutas humanas nessa área e a temida limpeza racial. Diante disso, o presente trabalho faz o contraponto entre a concepção bioconservadora de Jürgen Habermas e a concepção liberal de Ronald Dworkin, considerando os antagonismos de ambas as teorias sob o ponto de vista ético e moral. Após contextualizar o problema no horizonte filosófico, em primeiro lugar, são apresentados os argumentos habermasianos contra a eugenia liberal através da análise da obra O Futuro da Natureza humana: a caminho de uma eugenia liberal? Explicitam-se os argumentos de Habermas em favor de uma ética da espécie a partir dos conceitos de igualdade, reciprocidade, autonomia, autodeterminação, dignidade, além da autocompreensão dos indivíduos como seres livres e iguais. Busca-se, portanto, reconstruir a estratégia argumentativa habermasiana. Posteriormente, criticam-se os argumentos bioconservadores de Jürgen Habermas, principalmente em relação à eugenia positiva (melhoramento humano) e ao fundamento de suas ideias em relação à compreensão normativa das relações humanas. Aborda-se o debate em torno da questão de pós-humanidade com apoio na teoria liberal de Ronald Dworkin, uma vez que tal estágio é considerado consequência da biotecnologia e perfaz um ponto crucial de discórdia entre ambas as teorias. O filósofo estadunidense firma a sua posição a favor de um direito à liberdade reprodutiva e, em consequência, favorável à submissão dos meios de melhoramento humano à liberdade de escolha individual. Assim sendo, este trabalho pretende fornecer elementos para que se constatem os limites da manipulação genética, de modo que cabe à moralidade e à ética preencher o vácuo do destino criado pela biotecnologia, tendo como fim a manutenção da espécie e da natureza humana.
Keywords: Habermas, Jürgen, 1929-; Dworkin, Ronald William, 1931-2013; Eugenia; Ciência - Filosofia; Bioética; Eugenics; Science - Philosophy; Bioethics